Synthesis and biological evaluation of a trisaccharide repeating unit derivative of Streptococcus pneumoniae 19A capsular polysaccharide. Issue 21 (15th November 2018) - Morelli, Laura; Fallarini, Silvia; Lombardi, Grazia; Colombo, Cinzia; Lay, Luigi; Compostella, Federica
Graphical abstract: Highlights: An aminopropyl derivative of the trisaccharide repeating unit of SP 19A was synthesized. Two synthetic strategies based on different disconnections between the three monosaccharides were compared. The binding affinity of the synthesized trisaccharide towards anti-19A and anti-19F sera was evaluated. Abstract: Streptococcus pneumoniae (SP) is a common human pathogen associated with a broad spectrum of diseases and it is still a leading cause of mortality and morbidity worldwide, especially in children. Moreover, SP is increasingly associated with drug resistance. Vaccination against the pathogen may thus represent an important strategy to overcome its threats to human health. In this context, revealing the molecular determinants of SP immunoreactivity may be relevant for the development of novel molecules with therapeutic perspectives as vaccine components. Serogroup 19 comprises the immune-cross reactive types 19F, 19A, 19B and 19C and it accounts for a high percentage of invasive pneumococcal diseases, mainly caused by serotypes 19F and 19A. Herein, we report the synthesis and biological evaluation of an aminopropyl derivative of the trisaccharide repeating unit of SP 19A. We compare two different synthetic strategies, based on different disconnections between the three monosaccharides which make up the final trisaccharide, to define the best approach for the preparation of the trisaccharide. Synthetic accessibility to the trisaccharide repeating unit lays the basis for the development of more complex biopolymer as well as saccharide conjugates. We also evaluate the binding affinity of the trisaccharide for anti-19A and anti-19F sera and discuss the relationship between the chemical properties of the trisaccharide unit and biological activity.